2017
DOI: 10.1111/aec.12492
|View full text |Cite
|
Sign up to set email alerts
|

How do predators and scavengers locate resource hotspots within a tropical forest?

Abstract: In many parts of the world, wildlife species congregate at 'hotspot' locations that offer feeding opportunities unmatched in the wider landscape. But to exploit those resource-rich sites, animals must first locate them. In tropical Australia, predators and scavengers (especially dingos, scrub turkeys, snakes, and invasive toads) gather beneath large canopy-emergent trees that house breeding colonies of metallic starlings (Aplonis metallica). Some wildlife species feed on fallen nestlings whereas others consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Starling colonies thus provide scattered hotspots of resource availability within the forest, with the same emergent trees being occupied by starling aggregations in successive years (Natusch et al ., 2016). Our previous papers on this system provide information about the spatial distribution and attributes of starling‐colony trees (Natusch et al ., 2016; Natusch et al ., 2017a,b,c,d; Lettoof et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Starling colonies thus provide scattered hotspots of resource availability within the forest, with the same emergent trees being occupied by starling aggregations in successive years (Natusch et al ., 2016). Our previous papers on this system provide information about the spatial distribution and attributes of starling‐colony trees (Natusch et al ., 2016; Natusch et al ., 2017a,b,c,d; Lettoof et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…revealed the taxonomic composition of the snake predators and discrepancies between detection and attack rates (Akcali et al., 2019). To examine predator‐specific attraction to prey auditory and olfactory cues, Natusch, Lyons, and Shine (2017) simulated metallic starling Aplonis metallica vocalizations and scent at camera trap stations, demonstrating that starling predators were primarily attracted to scent cues. Predator diversity and consequences of predation on prey demography can also be assessed by stocking and monitoring a population of focal prey; camera traps deployed on outdoor fish tanks and semi‐natural streams identified the primary predator of Masu salmon, the influence of habitat and time of day on attack rates, the role of prey density on predator visitation, and the demographic class most impacted by predation (Miyamoto et al, 2018; Figure 2).…”
Section: Experimental Applications Of Camera Traps To Predator–prey Ementioning
confidence: 99%
“…We believe the increasing perceptibility of kill sites best explains coyote use because olfactory cues and other direct cues, such as visual detection of avian scavengers, should increase shortly after the kill, which corresponds precisely with the pattern of increased use we observed with coyotes. Other work has indicated that even for a highly concentrated and predictable resource, the absence of direct cues can dramatically decrease the use of an area by scavengers (Natusch et al, 2017 ). Thus, it is possible that in many systems, neither memory of the particular areas where resources were located nor associating resources with their related habitats are used alone to locate resources.…”
Section: Discussionmentioning
confidence: 99%
“…First, we tested whether coyotes selected or avoided mountain lions and kills made by mountain lions based on direct or indirect assessments of their presence on the landscape. Being Canids, coyotes should be well equipped to locate carrion directly based on the presence of strong olfactory and visual cues (Danner & Smith, 1980 ; Kamler et al, 2004 ; Natusch et al, 2017 ), but coyotes may be limited in their ability to detect mountain lions. Mountain lions are stalk‐and‐ambush predators (Beier et al, 1995 ), and should be difficult to perceive directly, but should occupy somewhat predictable habitats (Makin et al, 2017 ; Preisser et al, 2007 ) and thus be more perceptible via indirect means.…”
Section: Introductionmentioning
confidence: 99%